Biomarkers in Patients with Metastatic Breast Cancer and the PRAEGNANT Study Network - Fasching, P. A.; Brucker, S. Y.; Fehm, T. N.; Overkamp, F.; Janni, W.; Wallwiener, M.; Hadji, P.; Belleville, E.; Häberle, L.; Taran, F.-A.; Lüftner, D.; Lux, M. P.; Ettl, J.; Müller, V.; Tesch, H.; Wallwiener, D.; Schneeweiss, A. (Geburtshilfe und Frauenheilkunde, 2015)
Progress has been made in the treatment of metastatic breast cancer in recent decades, but very few therapies use patient or tumor-specific characteristics to tailor individualized treatment. More than ten years after the publication of the reference human genome sequence, analysis methods have improved enormously, fostering the hope that biomarkers can be used to individualize therapies and offer precise treatment based on tumor and patient characteristics. Biomarkers at every level of the system (genetics, epigenetics, gene expression, micro-RNA, proteomics and others) can be used for this. This has led to changes in clinical study designs, with drug developments often only focusing on small or very small subgroups of patients and tumors. The screening and registration of patients and their molecular tumor data has therefore become very important for the successful completion of clinical studies. This new form of medicine presents particular challenges for patients and physicians. Even in this new age of genome-wide analysis, the focus should still be on the patientsʼ quality of life. This review summarizes recent developments and describes how the PRAEGNANT study network manages the aforementioned medical challenges and changes to create a professional infrastructure for patients and physicians.
Keywords: breast cancer; metastasis; PRAEGNANT; mutation; biomarker; prognosis